The Grandmaster Experiment. - Flora, Carlin (Psychology Today)
A profile of Hungarian sisters Susan, Judit, and Sophia Polgar, three of the most successful female chess players ever. The writer discusses how the sisters' father, Laszlo Polgar, nurtured a love of chess in the trio, the various factors that led to the success of the sisters in chess, and how gender can affect a person's chess ability.